PENCITRAAN BANGSA JERMAN DALAM NOVEL “GENERATION GOLF - Desti Nur Aini; Dudy Syafruddin (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This research is aimed at describing the various stereotypes, prejudices, and ethnocentrism which appeared in the character in the novel “Generation Golf”. The qualitative approach was applied in this research. Note reading technique was a technique used for data collection. The data analysis method was domain analysis. The result of the research indicates that there are kinds of stereotypes, prejudice and ethnocentric attitudes. Stereotypes appeared are learding to negative and positive kinds; kinds of prejudice appeared in the form of negative feelings, beliefs and actions; and ethnocentric attitudes are raised by attributing German’s culture with other nations